Anthropometric characteristics of four groups of indigenous people of Wallacea in East Indonesia - Rahmawati, Neni Trilusiana; Hastuti, Janatin; Suriyanto, Rusyad Adi (Anthropological Review, 2023)
The human body size varies significantly around the world, both between and within populations. Likewise, ethnic diversity has a significant effect on anthropometric data differences for the Naulu, Tana Ai, Bugis and Rampasasa tribes, in Wallacea, East Indonesia. Six body dimensions were collected from 484 people, 219 males and 265 females in the age from 18 to 80 years. The statistical analysis included tabulating the means and standard deviations for the various body dimensions and proportions. A one-way ANOVA with post hoc LSD test was performed to determine significant differences between the means of anthropometric dimensions and proportions, as well as within the four ethnic groups. There are significant differences (p